Health Practitioner Notification of Competence Concerns: Career Suicide v Patient Safety? - Miller, Anita (Victoria University of Wellington Law Review, 2016)
This article examines the discretionary notification of competence concerns by health practitioners, through the lens of patient safety. The discretion, provided for in the Health Practitioners Competence Assurance Act 2003, is discussed alongside ethical obligations, factors that may inhibit raising concerns about substandard practice, and the arguments for and against mandatory reporting of incompetent practice. It concludes that the absence of a statutory obligation to notify such concerns creates a risk that problems will go unreported and that patients may be exposed to harm. Comprehensive research into the source of notifications, and practitioners understanding of the threshold for raising concerns, is recommended. It is also suggested that legislative change to require mandatory reporting in certain circumstances may need to be reconsidered.